Implementasi Metode Certainty Factor dan Forward Chaining untuk Mendeteksi Kerusakan Mesin Motor Matic Injeksi Berbasis Website - Andi Tri Wibowo (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Motor Matic Injection is a two-wheeled motorized vehicle that is favored by the community, especially among women, the lack of knowledge is one of the factors in the community so that they often ignore damage to the motor engine, the impact of which is more severe damage to the engine. In this study, the researcher uses the divorce factor method to calculate the confidence level of a rule and the forward chaining method that matches the damage or symptoms felt by the user to test the truth of the hypothesis so as to produce several solutions. From the results of the research that has been done, a web-based application is produced that can be used to diagnose damage to the Matic motorcycle engine.